The sum of 2ab^2 and (-5ab^2) is the same as the sum of (-6ab^2) and

Question

The sum of 2ab^2 and (-5ab^2) is the same as the sum of (-6ab^2) and

in progress 0
Alaia 21 hours 2021-10-13T05:13:51+00:00 1 Answer 0

Answers ( )

    0
    2021-10-13T05:15:14+00:00

    Answer:

    ? = 3ab^2

    for  the sum of (-6ab^2) and 3ab^2

    Step-by-step explanation:

    2ab^2 +(-5ab^2) =(-6ab^2)  +  ?

    -3ab^2 = -6ab^2 +  ?

    ? = 6ab^2 – 3ab^2

    ? = 3ab^2

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )